2022
DOI: 10.1021/acsphotonics.2c01228
|View full text |Cite
|
Sign up to set email alerts
|

Highly Monodisperse PbS Quantum Dots with Facet Engineering for High-Radiance Light-Emitting Diodes in the NIR-II Window

Abstract: Solution-processed PbS quantum dot light-emitting diodes (QLEDs) with emission in the second near-infrared window (NIR-II, 1100–1700 nm) are excellent candidates as light sources for optical communication, night vision, and biomedical monitoring. However, it is still a tremendous challenge to achieve high-radiance PbS QLEDs due to serious QD surface traps and unbalanced charge injection. Herein, highly monodisperse PbS QDs with tailored facet growth were successfully synthesized by the continuous precursor inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Two distinct architectural platforms have been employed for the development of QD-based NIR-LEDs, namely, planar and blend architectures. In planar architecture, an ultrathin emitter QD layer is sandwiched between electron and hole-injecting layers; ,, whereas in a blend configuration, narrow-bandgap emitter QDs dispersed in the matrix of the high-bandgap semiconductor layer are sandwiched between electron and hole injecting layers. , The planar architecture favors the balanced injection of electrons and holes in the thin emitter QD layer; however, it suffers from higher nonradiative pathways. Carrier delocalization within the electronically coupled emissive QD layer and nonradiative recombination via a few faulty emitter QDs in the emissive layer can significantly reduce the PL and EL emission of the planar device architecture.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two distinct architectural platforms have been employed for the development of QD-based NIR-LEDs, namely, planar and blend architectures. In planar architecture, an ultrathin emitter QD layer is sandwiched between electron and hole-injecting layers; ,, whereas in a blend configuration, narrow-bandgap emitter QDs dispersed in the matrix of the high-bandgap semiconductor layer are sandwiched between electron and hole injecting layers. , The planar architecture favors the balanced injection of electrons and holes in the thin emitter QD layer; however, it suffers from higher nonradiative pathways. Carrier delocalization within the electronically coupled emissive QD layer and nonradiative recombination via a few faulty emitter QDs in the emissive layer can significantly reduce the PL and EL emission of the planar device architecture.…”
Section: Introductionmentioning
confidence: 99%
“…17 Conducting ligand passivation is achieved via engineering the QD surface with small or atomic dimension ligands, which reduces the hopping potential to increase carrier mobility in solid films. 1,26,33 The conducting surface ligands enable efficient carrier injection to emitter QDs; however, increased coupling between QDs reduces carrier confinement to decrease their PLQY and limit the EL emission. 1,26 Two distinct architectural platforms have been employed for the development of QD-based NIR-LEDs, namely, planar and blend architectures.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, high-performance PbS-based QLEDs with maximum EQE of 18% were achieved by mixing PbS CQDs with different bandgaps and sizes. , However, the high EQE values were achieved only when the current density was lower than 1 mA/cm 2 , leading to limited achievable radiances. EQEs of over 0.5% under large current density (>1000 mA/cm 2 ) were rarely reported in PbS-based QLEDs with an emission peak approaching 1550 nm. , Previous work showed that breakthrough radiances of 16.1 W/sr –1 /m –2 and 0.3% EQE under >1000 mA/cm 2 current density were achieved in QLEDs based on PbS-CQDs with suppressed (100) facets . This suggested that the protection of the naked (100) facets was important to achieve high-radiance PbS-based QLEDs.…”
mentioning
confidence: 99%
“…Ligand exchange with halogen ions was applied to passivate the surface traps and improve the carrier mobility of PbS CQDs. , However, PbS CQDs with too short ligands can easily aggregate and increase the carrier delocalization extensively, which brings benefits in PbS-based solar cells but causes the problem of poor exciton confinement in PbS-based QLEDs. The regulation of kinetic-driven nanocrystal growth was also reported to suppress the amount of (100) facets. However, (100) facets cannot be fully suppressed. Therefore, a facile way of protecting the weakly self-passivated (100) facets without replacing the long-chain ligands is still urgently needed to fabricate high-performance PbS-based QLEDs emitting in the shortwave infrared region.…”
mentioning
confidence: 99%